The Role of Fintech on Enchancing Financial Literacy and Inclusive Financial Management in MSMEs - Hamid, Abdul; Widjaja, Warkianto; S, Sutrisno; Napu, Fitriah; Sipayung, Baren (PT.KARYA GEMAH RIPAH, 2024)
Fintech has transformed the global financial sector, providing more efficient, inclusive, and accessible financial services. Fintech has great potential to improve access to financial services, financial literacy, and more effective financial management for Micro, Small, and Medium Enterprises (MSMEs). MSMEs often experience barriers in accessing traditional financial services, which can hinder their business growth and sustainability. Fintech offers solutions that are more flexible and tailored to the needs of MSMEs, such as online loans with lighter terms, digital payment systems that facilitate transactions, and financial management applications that assist MSMEs in managing their finances more effectively. In addition, fintech also plays a role in improving MSMEs' financial literacy through digital financial education and training, which is crucial in helping them make informed financial decisions. This research uses descriptive method and literature analysis. Data was received from other studies that reviewed the role of fintech in the context of MSMEs. The results show that fintech has great potential to improve access to financial services, especially in developing countries. Fintech can improve the operational efficiency of MSMEs through solutions such as digital payments and financial process automation, which can help MSMEs save time and costs, and increase productivity. The urgency of improving MSMEs' knowledge and utilization of fintech is high, given the important role of MSMEs in the economy and the potential of fintech in supporting their business growth.